Historical analysis of the acquisition of rural properties by foreigners in Brazil: contribution to Critical Agrarian Studies - Lourenço, Welington Batista [UNESP]; Maniglia, Elisabete [UNESP] (Universidad Nacional de La Plata, 2022)
This article seeks to investigate, from a historical approach, how the legal regime for the acquisition of rural properties by foreigners evolved in the Brazilian legal system and how it is currently regulated by Brazilian legislation. It aims to establish bases for the development of future studies that relate the acquisition of rural properties by foreigners in Brazil to critical issues of agrarian law, such as land grabbing, agrarian extractivism, food sovereignty and climate changes. It is, therefore, a descriptive research. The methodology used was a non-systematized bibliographic and documentary review. At the end of the research, it was identified that the regime for the acquisition of rural properties by foreigners evolved from a paradigm of encouraging immigration and facilitating the acquisition of property by foreigners in Brazil to a regime of restriction on the acquisition of rural properties by foreigners
Análise histórica da aquisição de imóveis rurais por estrangeiros no Brasil: contribuição aos Estudos Agrários Críticos
Keywords: Acquisition; Agrarian History; Brazil; Foreign; Rural Land